An emerging perspective on 'histone code' mediated regulation of neural plasticity and disease. (December 2019) - Farrelly, Lorna A; Maze, Ian
Highlights: Histone regulation in brain is a central determinant of neural development and plasticity. Many neurological diseases are linked to aberrant histone regulation in the CNS. New methods for investigating histones may help to causally link them to biological function. Abstract : The last two decades have witnessed explosive advances in our understanding as to how the organization of chromatin, the association of DNA with histones and vast numbers of non-histone regulatory proteins, controls the expression of specific genes in brain. Prominent among such regulatory mechanisms are modifications of histones, along with the 'writers, ' 'erasers, ' and 'readers' of these modifications. Much of the work delineating these mechanisms has contributed to the idea that a 'histone code' may be a central determinant of a gene's activity and its potential to be activated or repressed in response to environmental perturbations (both beneficial and aberrant). Indeed, increasing evidence has demonstrated the significance of histone regulation in neurological plasticity and disease, although we are still at the earliest stages of examining all of the many potential chromatin changes involved. In this short review, we provide an emerging perspective on putative roles for histones, and their combinatorial readouts, in the context of neural plasticity, and we provide a conceptual framework for future mechanistic studies aimed at uncovering causal links between the neural 'histone code' and brain function/disease.